Examination of recreation levels of university students with regard to various variables - Yildiz, Mustafa; Sahan, Hasan; Tekin, Murat; Devecioglu, Sebahattin; Yarar, Demet Neriman (Elsevier Science Bv, 2012)
The objective of this study is to examine recreation levels of university students with regard to various variables. 503 university students in total including 248 girls and 255 boys receiving education in various faculties and graduate schools of Karamanoglu Mehmet Bey University, Inonu University, Gazi University and 19 Mayis University constitute the research group. The questionnaire developed by researcher was employed to achieve study objective. Significance was extracted P<0.05 by employing Chi-Square test (2X2) in solution and interpretation of data. SPSS (Statistical package for social sciences) package software was used in assessment of data and finding the calculated values. It was inferred as a result of this study that male students in comparison with female students and students receiving education in the faculty of education in comparison with the ones, who receive education in other departments, enjoy participating in social activities, improve their personal skill and capabilities by participating in social activities, participate in sportive activities, consider attending socio-cultural activities important and are more active in terms of cultural activity. These outcomes demonstrate that individuals freely take part in recreative activities.
4th World Conference on Educational Sciences (WCES) -- FEB 02-05, 2012 -- Univ Barcelona, Barcelona, SPAIN
Keywords: University; Sutudent; Recreation